Asymmetric C‐Alkylation by the S‐Adenosylmethionine‐Dependent Methyltransferase SgvM. (1st March 2017) - Sommer‐Kamann, Christina; Fries, Alexander; Mordhorst, Silja; Andexer, Jennifer N.; Müller, Michael
Abstract: S ‐Adenosylmethionine‐dependent methyltransferases (MTs) play a decisive role in the biosynthesis of natural products and in epigenetic processes. MTs catalyze the methylation of heteroatoms and even of carbon atoms, which, in many cases, is a challenging reaction in conventional synthesis. However, C‐MTs are often highly substrate‐specific. Herein, we show that SgvM from Streptomyces griseoviridis features an extended substrate scope with respect to the nucleophile as well as the electrophile. Aside from its physiological substrate 4‐methyl‐2‐oxovalerate, SgvM catalyzes the (di)methylation of pyruvate, 2‐oxobutyrate, 2‐oxovalerate, and phenylpyruvate at the β‐carbon atom. Chiral‐phase HPLC analysis revealed that the methylation of 2‐oxovalerate occurs with R  selectivity while the ethylation of 2‐oxobutyrate with S ‐adenosylethionine results in the S  enantiomer of 3‐methyl‐2‐oxovalerate. Thus SgvM could be a valuable tool for asymmetric biocatalytic C‐alkylation reactions.